2003
DOI: 10.1002/pca.685
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of the Chinese herb Langdu by LC‐MS/MS analysis

Abstract: An LC-MS/MS method has been developed for the identification of three species of herb used as the traditional Chinese medicine Langdu, namely Stellera chamaejasme L., Euphorbia ebracteolata Hayata and E. fischeriana Steud. As these herbs contain different mixtures of marker compounds, they could be unambiguously differentiated from each other by comparing their respective characteristic segmental multiple reaction monitoring profiles. The profiles indicated that S. chamaejasme contained daphnetin, skimmetine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…Zhao et al [5] detected 22 isolated chromatography peaks in the total ion current chromatogram (TIC) and nine of them were characterized by RPLC-DAD tandem ESI-Q-TOF-MS. And because of the unavailability of commercial reference standards and the lack of multi-grade fragmentation ability of Q-TOF instrument, diterpenes could not be identified and the reliability of identification results which only based on the accurate molecular weights was doubtable in some degree. Su et al [6] characterized and compared the chemical constitutes of three Chinese herbs "Langdu" (Stellera chamaejasme, Euphorbia fischeriana, and Euphorbia ebracteolata) by LC-MS/MS analysis, but this investigation mainly focused on developing the analytical strategy in the light of respective makers for differentiating these three herbs from the related species. In addition to that, no related literature about the characterization of chemical components in S. chamaejasme depicted the systematic MS n fragmentation patterns of different types of compounds and inferred some unknown ingredients on the basis of mass fragmentation of reference compounds.…”
mentioning
confidence: 99%
“…Zhao et al [5] detected 22 isolated chromatography peaks in the total ion current chromatogram (TIC) and nine of them were characterized by RPLC-DAD tandem ESI-Q-TOF-MS. And because of the unavailability of commercial reference standards and the lack of multi-grade fragmentation ability of Q-TOF instrument, diterpenes could not be identified and the reliability of identification results which only based on the accurate molecular weights was doubtable in some degree. Su et al [6] characterized and compared the chemical constitutes of three Chinese herbs "Langdu" (Stellera chamaejasme, Euphorbia fischeriana, and Euphorbia ebracteolata) by LC-MS/MS analysis, but this investigation mainly focused on developing the analytical strategy in the light of respective makers for differentiating these three herbs from the related species. In addition to that, no related literature about the characterization of chemical components in S. chamaejasme depicted the systematic MS n fragmentation patterns of different types of compounds and inferred some unknown ingredients on the basis of mass fragmentation of reference compounds.…”
mentioning
confidence: 99%
“…Mass spectrometric techniques have been widely used for identification of traditional Chinese herbal medicines, because of their high sensitivity and fast screening capabilities in detecting target compounds in complex systems. Su et al reported that 10 compounds from the three species of Langdu were identified by LC-MS/MS (Su et al, 2003), but multiple constituents in the root of Stellera chamaejasme L. have not been defined. Accurate mass measurement, such as TOF/MS, greatly increases the confidence of identification because it inherently limits the possible number of candidate compounds; the better precision and accuracy of the mass measurement, the fewer compounds will be theoretically possible.…”
Section: Introductionmentioning
confidence: 97%
“…It was reported that biflavonoids had anti-inflammatory, antiviral, cytotoxic, and antioxidative activity [5][6][7]. Chamaechromone, a biflavone constituent, was a major component in dried roots of S. chamaejasme [8], and it was found that it showed anti-HBV effect against HBsAg secretion [9].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them were based on liquid chromatography-mass spectrometry (LC-MS) [8], rapid-resolution liquid chromatography-diode array detection (RRLC-DAD) and electrospray ionization time-of-flight mass spectrometry (ESI-TOF/MS) [10], high performance liquid chromatography with ultraviolet detection (HPLC-UV) [11], highresolution ESMS [11] and NMR spectrometry [11,12] for detection and identification of the constituents. Until now, no method has been reported on pharmacokinetic study.…”
Section: Introductionmentioning
confidence: 99%